Parametric analysis of rotary VTOL aerobot design configurations to fly on Titan - Youhanna, Vishal; Felicetti, Leonard; Ignatyev, Dmitry (International Astronautical Federation (IAF), 2024)
The exploration of Titan, Saturn’s largest moon, presents significant aerodynamic challenges due to its dense atmosphere and low gravity, necessitating specialised rotorcraft designs. This study conducts a parametric analysis of multiple rotary Vertical Takeoff and Landing (VTOL) aerobot configurations, including conventional helicopters, coaxial systems, tandem rotorcraft, quadcopters, and hexacopters, with a focus on performance in Titan's environment. Using simplified momentum theory, the power consumption and operational efficiency of these rotorcraft are evaluated across key flight phases such as vertical climb, hover, and forward flight. The analysis highlights that hexacopter configurations are the most power-efficient during vertical ascent and hover for smaller rotor diameters, whereas conventional helicopter designs excel in forward flight for larger rotor sizes. The study also utilises Battery Mass Fraction (BMF) calculations to assess the energy requirements for various flight segments, offering valuable insights into the energy-efficient design of rotorcraft for Titan exploration. This research establishes a foundational framework for optimising rotorcraft design in extraterrestrial environments, providing critical data for future missions aimed at exploring Titan’s surface and atmosphere.
Keywords: Titanian aerial drones; planetary UAV; rotorcraft conceptual design